Uji Karakteristik Biobriket Berbahan Baku Tongkol Jagung dan Cangkang Kemiri: Uji Karakteristik Biobriket Berbahan Baku Tongkol Jagung dan Cangkang Kemiri - Gobel, Siti Amalia; K Rahmawati, Fathiin; Anwar, Rustam; SM, Farid (Jurnal Biogenerasi, 2024)
This research aims to make charcoal briquettes from corn cob organic waste, determine the right type of adhesive to make corn cob charcoal briquettes to produce good quality briquettes, determine the right percentage of adhesive to produce corn cob briquettes to produce good quality briquettes. good and know the characteristics of the best corncob charcoal briquettes which include water content, volatile matter content, ash content, bound carbon content and calorific value. The sample used was corn cob waste obtained from a corn farmer in Botuwombato Village, North Gorontalo Regency. This research uses experimental methods in the laboratory with several stages, namely: material preparation, carbonization, crushing and sieving charcoal, mixing charcoal with adhesive and water, briquetting, drying briquettes, and analyzing the quality of briquettes. From the research results, it was found that alternative energy sources, namely charcoal briquettes, can be made from biomass waste from agricultural waste of corn cobs and candlenut shells. The moisture content of candlenut shell charcoal briquettes is around 14.15% and the moisture content of corn cob charcoal briquettes is around 10.29%. , The test results of the calorific value of candlenut shell charcoal briquettes are around 4173 cal/gr and the calorific value of corn cob briquettes is around 7630 cal/gr.